Evaluasi Pelaksanaan Pengembangan Managemen SDM dalam Meningkatkan Prestasi Kerja Pegawai; Studi Kasus Biro Umum Sekretariat Daerah Provinsi Sumatera Utara - Khinaya, Mutiara; Yafiz, Muhammad; Marliyah, Marliyah (State of Islamic Institute Langsa, 2024)
Ideally, human resource management (HRM) development within the government sector should improve employee performance through structured and targeted programs such as education and training (diklat), technical guidance, and seminars that support skill enhancement and work quality. However, in reality, at the General Bureau of the Regional Secretariat of North Sumatra, HRM development is often poorly organized and not aligned with employees' work schedules, leading to inefficiency in achieving organizational goals. The purpose of this study is to evaluate the existing HRM development implementation model and to identify the evaluations carried out to improve employee performance. This research uses a qualitative approach with a descriptive study methodology. The findings show that the implementation model of HRM development at the General Bureau of the Regional Secretariat of North Sumatra has not been optimally implemented. Evaluations of HRM development programs reveal a mismatch between the implementation of the programs and the employees' needs, as well as a lack of sufficient financial support for development activities.